JUMLAH UANG SAKU DAN KEBIASAAN MELEWATKAN SARAPAN BERHUBUNGAN DENGAN STATUS GIZI LEBIH ANAK SEKOLAH DASAR - Zia Rosyidah; Dini Ririn Andrias (Media Gizi Indonesia, 2015)
The prevalence of overnutrition in Indonesia is increasing from year to year. Overnutrition occurs because of an imbalance between consumed and expended energy. Overnutrition needs a serious attention because it deals with a variety of health problem complications in adult, such as diabetes and heart disease. This research aims to analyze the association between the amount of pocket money and breakfast habit with overnutrition status in elementary school children. Analytical observational research with cross sectional design was conducted in SDN Ploso I-172 Tambaksari Surabaya. The sample size was 52, which was taken by using simple random sampling technique in 4th and 5th grade students. Association among variables were analyzed using Chi-Square test. The result showed that 32.7% of respondents skip breakfast. The mean of respondent’s pocket money was IDR 5.894,23 ± 3.215,06. Majority of respondents were obese (34.6%) and overweight (28.8%). Chi-Square test showed there was an association between the amount of pocket money (p=0.000) and breakfast habits (p=0.005) with overnutrition status. It can be concluded that the amount of pocket money and breakfast skipping habit contribute to overnutrition status in elementary school children. Parents are responsible for providing foods with adequate nutrition for children, habituate children to have breakfast at home, and provide pocket money to children with amount less than IDR 5.894,23 ± 3.215,06.Keywords: breakfast, overnutrition status, pocket money